Evidence for slow late-glacial ice retreat in the upper Rangitata Valley, South Island, New Zealand. (1st April 2018) - Shulmeister, J.; Fink, D.; Winkler, S.; Thackray, G.D.; Borsellino, R.; Hemmingsen, M.; Rittenour, T.M.
Abstract: A suite of cosmogenic radionuclide ages taken from boulders on lateral and latero-terminal moraines in the Rangitata Valley, eastern South Island, New Zealand demonstrates that relatively thick ice occupied valley reaches inland of the Rangitata Gorge until c. 21 ka. Thereafter ice began to thin, and by c. 17 ka it had retreated 33 km up-valley of the Rangitata Gorge to the Butler-Brabazon Downs, a structurally created basin in the upper Rangitata Valley. Despite its magnitude, this retreat represents a minor ice volume reduction from 21 ka to 17 ka, and numerous lateral moraines preserved suggest a relatively gradual retreat over that 4 ka period. In contrast to records from adjacent valleys, there is no evidence for an ice-collapse at c. 18 ka. We argue that the Rangitata record constitutes a more direct record of glacial response to deglacial climate than other records where glacial dynamics were influenced by proglacial lake development, such as the Rakaia Valley to the North and the major valleys in the Mackenzie Basin to the south-west. Our data supports the concept of a gradual warming during the early deglaciation in the South Island New Zealand. Highlights: Exceptional preservation of last deglaciation sequence in protected valley location in South Island, New Zealand. CRN chronology demonstrates gradual ice retreat in the Rangitata Valley between 21 and 17 ka. Supports concept of gradual rather than abrupt warming at the end of the last glaciation in New Zealand.